Identification of a divergent environmental DNA sequence clade using the phylogeny of gregarine parasites (Apicomplexa) from crustacean hosts. - Sonja Rueckert (Public Library of Science (PLoS), 2011)
Background Environmental SSU rDNA surveys have significantly improved our understanding of microeukaryotic diversity. Many of the sequences acquired using this approach are closely related to lineages previously characterized at both morphological and molecular levels, making interpretation of these data relatively straightforward. Some sequences, by contrast, appear to be phylogenetic orphans and are sometimes inferred to represent "novel lineages" of unknown cellular identity. Consequently, interpretation of environmental DNA surveys of cellular diversity rely on an adequately comprehensive database of DNA sequences derived from identified species. Several major taxa of microeukaryotes, however, are still very poorly represented in these databases, and this is especially true for diverse groups of single-celled parasites, such as gregarine apicomplexans. Methodology/principal findings This study attempts to address this paucity of dna sequence data by characterizing four different gregarine species, isolated from the intestines of crustaceans, at both morphological and molecular levels: Thiriotia pugettiae sp. n. from the graceful kelp crab (Pugettia gracilis), Cephaloidophora cf. communis from two different species of barnacles (Balanus glandula and B. balanus), Heliospora cf. longissima from two different species of freshwater amphipods (Eulimnogammarus verrucosus and E. vittatus), and Heliospora caprellae comb. n. from a skeleton shrimp (Caprella alaskana). SSU rDNA sequences were acquired from isolates of these gregarine species and added to a global apicomplexan alignment containing all major groups of gregarines characterized so far. Molecular phylogenetic analyses of these data demonstrated that all of the gregarines collected from crustacean hosts formed a very strongly supported clade with 48 previously unidentified environmental DNA sequences. Conclusions/significance This expanded molecular phylogenetic context enabled us to establish a major clade of intestinal gregarine parasites and infer the cellular identities of several previously unidentified environmental SSU rDNA sequences, including several sequences that have formerly been discussed broadly in the literature as a suspected "novel" lineage of eukaryotes.